Spring departure date, not en route conditions, drive migration rate and arrival timing in a long-distance migratory songbird - Turcotte-van de Rydt, Christophe; Muthukumarana, Saman; Fraser, Kevin C. (Frontiers in Bird Science, 2023)
Long-distance avian migrants are threatened by a rapidly changing environment, which can induce a mismatch between favorable environmental conditions and the timing of breeding. Therefore, migratory birds must rely on phenotypic plasticity within migration timing to remain synchronized with earlier occurring resources over the shorter term. However, how this plasticity responds to en route environmental factors and whether it may allow migratory birds to remain synchronized with advancing springs is largely unknown. The objective of this study was to investigate how extrinsic factors such as weather (e.g., temperature, precipitation, wind) and daylength experienced along spring migration routes, and intrinsic factors such as sex and age, migration departure date from wintering grounds, and migration destination (i.e., breeding site), influence migration-wide migration rate, spring arrival date at the breeding grounds in purple martin (Progne subis). We investigated arrival timing and rate using 307 individual migration tracks sampled across their eastern breeding range. We found that departure date and time at stopovers explained most of the variation in migration rate, with later birds traveling faster and more stop days leading to a slower overall rate. To a lesser extent, facilitating southern winds and lower precipitation also induced a faster migration rate. We found that birds with a faster migration rate arrived earlier at their breeding sites. We also found that females traveling to more northern breeding sites arrive earlier than males, i.e., protogyny, and migrate faster. Overall, our results suggest that migration rate may be most impacted by intrinsic factors tied to spring departure dates that are aligned with the phenology of breeding sites rather than by conditions experienced en route. These findings support growing evidence that selection on spring departure date may be needed for the advancement of spring arrival date to match advancing springs with climate change. Future research investigating how environmental conditions at stopovers contribute to the overall migration rate would provide further insight into factors influencing migration timing.